Treatment of Classic Syndromes in Idiopathic Focal Epilepsies in Childhood - Valeta, Thalia; Panayiotopoulos, C. P. (Journal of Pediatric Epilepsy, 2016)
Of the classic syndromes of idiopathic (benign) focal epilepsies in childhood, more than half of children with Rolandic epilepsy and Panayiotopoulos syndrome do not need antiepileptic drug (AED) treatment. Monotherapy with carbamazepine, levetiracetam, sodium valproate, or clobazam is usually recommended for those with seizures that are unusually frequent (more than three), lengthy, distressing, or otherwise significantly interfering with the child's life. Other factors in favor of treatment include a short interval between the first three seizures, a younger age of onset (less than 4 years), or a presence of recurrent tonic–clonic seizures and diurnal seizures. In contrast to Rolandic epilepsy and Panayiotopoulos syndrome that may not need treatment, idiopathic childhood occipital epilepsy of Gastaut should be treated because seizures are frequent and secondarily generalized convulsions are probably unavoidable without medication. It is likely that all AEDs licensed as monotherapy for focal seizures and mainly carbamazepine and levetiracetam are suitable.The electroencephalogram does not predict prognosis or AED treatment needs, though there are views supporting that interictal spikes have an adverse effect on cognition.Strategies of withdrawing medication in idiopathic focal epilepsies in childhood differ among experts, although all agree that there is no need to continue medication 1 to 3 years after the last seizure, and certainly not after the age of 14 years, when most benign childhood focal seizures remit, or age 16, when they are practically nonexistent.In the acute stage of status epilepticus, control of the seizures is of paramount importance. Convulsive status epilepticus is a life threatening condition and should be terminated as soon as possible. Autonomic status epilepticus needs thorough evaluation for proper diagnosis and management. Benzodiazepines, intravenously, in rectal or buccal preparations are commonly used to terminate long lasting seizures and status epilepticus. Early parental treatment is more effective than late emergency treatment. Buccal midazolam is probably the first choice medication for out-of-hospital termination of status epilepticus.Parental education and psychological support are the cornerstone of the optimal management because despite excellent prognosis, idiopathic focal epilepsies in childhood usually have a dramatic impact to parents.
Keywords: benign childhood focal seizures; treatment with antiepileptic drugs; parental reactions and needs; “Metamyth”©